Bottle Masala holds a special place in the East Indian Community - Mumbai Archive Project Team (Jio Institute, 2024)
In addition to their signature bottle masala, Veera and Natasha Almeida make fish masala, puri masala, and indyal (vindaloo) masala. Though various factory-made spice blends exist in the market, bottle masala remains uniquely East Indian and holds a special place in the East Indian community as a symbol of their culinary tradition and heritage.